Comparative load flow analysis of a 400/230 KV grid substation in Bangladesh - Khan, Rahat; Newaz, Abdullah Ibna; Haque, Mohd Fahim; Nafis, Nur Qutubul Alam (Brac University, 2021)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Electrical and Electronic Engineering, 2020.